2012
DOI: 10.5402/2012/183983
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Immunological Changes of Immunotherapy in Patients with Atopic Dermatitis: Randomized Controlled Trial

Abstract: Background. Immunotherapy has proven to be an useful tool in the management of allergic respiratory diseases; however, little has been studied in atopic dermatitis. Objective. To evaluate the clinical and immunological impact of immunotherapy with mites allergen extracts in atopic dermatitis. Methods. Patients with atopic dermatitis were assigned with computer-generated randomization to either of the following groups: (a) controls received only topical treatment with steroids and/or tacrolimus and (b) actively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1
11

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 29 publications
(30 reference statements)
2
24
1
11
Order By: Relevance
“…The trial by Sanchez-Caraballo and Cardona-Villa 412 reported a significant improvement in disease severity, measured using the SCORAD index, in the experimental group compared with the control group after 6 months (p = 0.03), but the magnitude of benefit cannot be found in the reported data. An unvalidated patient-reported subjective score was also used to assess disease severity in this study and there was a significant difference in severity between treatments in favour of specific immunotherapy (p = 0.01).…”
Section: Benefitscontrasting
confidence: 48%
See 3 more Smart Citations
“…The trial by Sanchez-Caraballo and Cardona-Villa 412 reported a significant improvement in disease severity, measured using the SCORAD index, in the experimental group compared with the control group after 6 months (p = 0.03), but the magnitude of benefit cannot be found in the reported data. An unvalidated patient-reported subjective score was also used to assess disease severity in this study and there was a significant difference in severity between treatments in favour of specific immunotherapy (p = 0.01).…”
Section: Benefitscontrasting
confidence: 48%
“…Eight participants in the immunotherapy group and six participants in the placebo group experienced worsening of skin inflammation that required mild topical corticosteroids. In the trial by Sanchez-Caraballo and Cardona-Villa, 412 16 local immediate reactions were observed in 11 patients in the first 3 months of treatment, whereas no systemic reactions were recorded. It was unclear in which groups these adverse events were observed.…”
Section: Harmsmentioning
confidence: 99%
See 2 more Smart Citations
“…La sensibilidad en orden de frecuencia fue a Alternaria alternata, Aspergillus fumigatus, Candida albicans, Cladosporium herbarum y Tricophyton mentagrophytes. 29 Esta prevalencia baja de sensibilidad a hongos encontrada en Medellín es similar a la encontrada en pacientes con asma o rinitis en el mundo 8,13,14 y se puede presentar aislada o en racimos con sensibilidad a varios hongos. Raras veces se encuentra sensibilización a hongos aislada; es más frecuente la sensibilidad concomitante con otros alérgenos.…”
Section: Antecedentesunclassified